PENGARUH BAURAN PEMASARAN (7P) TERHADAP KEPUTUSAN SEWA KENDARAAN DI PT SURYA SUDECO (TUNAS RENT) - Benny Osta Nababan; Dasmansyah Adyas; Muhlis Muhlis; Rully Adriana (Economicus : Jurnal Ekonomi dan Manajemen, 2022)
Fulfilling the need for transportation equipment is not only fulfilled by buying but, can also be done through a rental system. As a result, the vehicle rental business has become a very lucrative business opportunity, both corporate and individual. Efforts to seize a fairly large market share require the right strategy so that business owners can achieve the targets that have been set and can increase the number of management units (units in contract). This study aims to determine the effect of marketing variables (7P) on rental decisions at PT Surya Sudeco either partially or simultaneously. This study was also conducted to determine the marketing mix (7P) and how much the marketing mix (7P) can explain the vehicle rental decision at PT Surya Sudeco. The results of the T test show that among the independent variables (X) analyzed, only the product variable has a positive and partially significant effect on vehicle rental decisions. While the results of the F test show that the independent variable (X) simultaneously has a positive and significant effect on the dependent variable (Y). The value of the coefficient of determination (R Square) of 35.1% indicates the contribution of the influence of the independent variable simultaneously to the dependent variable. While the remaining 64.9% is the influence of other variables (residual/error values) outside of the variables studied.